On the spectrum of a model operator in Fock space - Rasulov, T. H.; Muminov, M. I.; Hasanov, M. (Methods of Functional Analysis and Topology, 2009)
A model operator H associated to a system describing four particles in interaction, without conservation of the number of particles, is considered. We describe the essential spectrum of H by the spectrum of the channel operators and prove the Hunziker-van Winter-Zhislin (HWZ) theorem for the operator H. We also give some variational principles for boundaries of the essential spectrum and interior eigenvalues.